Potensi Sel Punca dalam Regenerasi Tulang: Perspektif Anatomi Mikroskopis: Stem Cell Potential in Bone Regeneration: A Microscopic Anatomic Perspective - Yana, Dian Rudy; Riwayati, Indah (Chakra Brahmanda Lentera Institute, 2026)
Bone is a dynamic tissue that undergoes constant remodeling to maintain structural strength, mineral homeostasis, and hematopoietic function. Disorders like complex fractures, osteoporosis, and bone defects resulting from trauma or surgery pose significant clinical challenges. Traditional treatments such as autografts, allografts, and synthetic biomaterials have limitations in terms of availability, efficacy, and potential complications. This article aims to provide a comprehensive overview of the intricate relationship between bone microscopic anatomy, stem cell biology, and biomedical engineering technologies, while also outlining future opportunities and challenges in developing more effective, safe, and sustainable bone regenerative therapies. This article was prepared through an integrative literature review of scientific publications from the 2020–2025 period to analyze the interactions between the bone microenvironment, stem cell differentiation mechanisms, and the development of biomaterial and bioprinting technologies in the context of bone regeneration. Recent advancements in cell biology and our understanding of microscopic anatomy have paved the way for stem cell-based regenerative therapies. Mesenchymal stem cells (MSCs) exhibit robust osteogenic capabilities through molecular regulation involving factors like Runx2, Osterix, BMP, and Wnt/β-catenin. Induced pluripotent stem cells (iPSCs) hold promise for personalized therapy, although safety concerns remain. The success of bone regeneration is heavily influenced by the bone microenvironment, including the vascular niche, extracellular matrix, and growth factors such as BMP-2, VEGF, PDGF, and TGF-β. Supporting technologies like biomaterial scaffolds, growth factor delivery systems, exosomes, and 3D bioprinting further enhance the potential for translating these therapies into clinical applications.